PENGARUH STRATEGI PRACTICE REHEARSAL PAIRS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII SMP AL-AZHAR - Saryantono, Buang; Noviyana, Hesti (LPPM STKIP PGRI Bandar Lampung, 2020)
The problem studied in this study is the low ability to solve mathematical problems, therefore the study aims to determine the effect of the Practice Rehearsal Pairs learning strategy on the mathematical problem solving ability of students of the VIII Even Semester SMP Al-Azhar 3 Bandar Lampung in the 2018/2019 Academic Year. Research using experimental methods. The population in the study were all students of class VIII Al-Azhar 3 Middle School Bandar Lampung consisting of 7 classes with a total of 251 students, while the sample was taken 2 classes namely class VIII C as an experimental class totaling 32, and class VIII C as a control class amounting to 34. The sample was taken using the Cluster Random Sampling technique. To find out the ability to solve mathematical problems students are measured by tests. Hypothesis testing uses t-test with a value of t = 12,62. From the distribution table t at a significant level of 5%, it is known that t = = 2,00 means t > t , so it can be concluded that